Oferta y promoción turística de la Parroquia Puela del Cantón Penipe. - Ruiz Meneses, Valeria Julissa (2022)
Tourism now a day is a fundamental part of the economy at the local, national and international levels; therefore, promotion is an indispensable part of publicizing the attractions that a city, parish, or town has. The research's main objective, "Tourist Offer and Promotion of the Puela parish in Penipe," is to determine the relationship between Tourist Offer and Promotion. The research methodology has a qualitative approach, transversal, and non-experimental methodological design; field research was applied, in addition, the survey technique and the questionnaire instrument were used to obtain informative data of the two variables, the dependent variable Tourism Promotion was directed to the inhabitants of the Puela parish; therefore a sample of the entire population of Puela was taken, while the independent variable Tourist Offer was directed to the staff of the Decentralized Autonomous Government of the Puela Rural Parish. With the results, several statistical methods were used, such as Cronbach's Alpha, to check the reliability of the instruments applied; these data were also processed and analyzed using the IBM SPSS Statistics version 22 program. The results obtained lead to the formulation of a proposal to design a marketing plan to increase the number of tourists in the Puela parish of the Penipe canton; this plan will contribute to the tourism and economic development of the parish, improving inhabitants' quality of life.